Pemetaan Informasi Sebaran Bidang Ilmu Pada Skripsi Fakultas Kedokteran Hewan Lulusan IPB University Tahun 2015-2019 Berdasarkan Standar Universal Decimal Classification: Suatu Kajian Bibliometrika - Azizah; Widiyati Kania (Jurnal Pustakawan Indonesia, 2020)
Introduction. Animal health and animal product safety currently becomes an important issue. The role of veterinarians in ensuring human health through animal health that can be transmitted to humans is needed. One of the faculties related to this issue at the Bogor Agricultural University is the Faculty of Veterinary Medicine (FKH), which has produced many basic, applied and strategic researches that support sustainable national development. There is no study that maps the results of research, so that the research repetition and unevenness of the studied areas have the potential to occur. It is necessary to map the student essay refers to the Universal Decimal Classification (UDC) standard. Methods and Data Collection. Data samples taken from IPB repository database for the last 5 (five) years, specifically 2015-2019 as many as 973 research titles. Data analysis. The scope of the study includes grouping data based on the field of science according to the Universal Decimal Classification (UDC) standard, Keyword analysis using VosViewer program visualization, department distribution analysis, the last is calculation of lecturer productivity in guiding student theses. Results and Discussion. The results of the study are number of the Faculty of Veterinary Medicine’ study in the period 2015-2019 was 973 titles. The most researched sub-fields of science related to "General Zoology" totaled to 591 (60.74%) research, while the least is related to "Industrial microbiology" as much as 3 (0.31%) research. VosViewer’s keyword relatedness visualization with at least 3 appearances showing 411 keyword items, divided into 15 clusters. The most often used keyword is "Medicinal plants" as much as 96 times with 297 relationships, but the least occurrences are "aedes aegypti" and "culex" as much as 3 times with 2 relationships. The highest productivity of supervisors for the 2015-2019 period was achieved by Aryani Sismin Satyaningtijas with a total of 55 mentors, consisting of 36 times as main supervisors and 19 times as mentors members.